Modern language journals in France and Germany around 1900: the construction of a public opinion within the teaching profession. - Mombert, Monique (Swiss Journal of Educational Research, 2018)
Around 1900, two educational journals in France (la Revue de l’Enseignement des Langues Vivantes and Les Langues Modernes) and one in Germany (Die Neueren Sprachen) offered a forum for debate for the teaching of modern languages. Their aim was to establish the public opinion of the teaching profession and a scientific ‘doctrine’ in this field. At a time when language teaching is affected by successive reforms and is the subject of much debate in society in general, the strategy of these journals is, depending on the circumstances, either defensive or offensive. This paper aims to analyse the journals in their context and examine their modes of exchange taking into account the games of scale that influence them.